Ability of Salmonella spp. to Produce Biofilm Is Dependent on Temperature and Surface Material - Vidal De Oliveira, Debora Cristina [UNESP]; Fernandes Junior, Ary [UNESP]; Kaneno, Ramon [UNESP]; Silva, Marcia Guimarães da [UNESP]; Araujo Junior, Joao Pessoa [UNESP]; Cirone Silva, Nathalia Cristina [UNESP]; Mores Rall, Vera Lucia [UNESP] (Mary Ann Liebert, Inc., 2014)
Salmonella, one of the most important pathogens transmitted by food, especially poultry, has the ability to form biofilms on surfaces. Its adhesion can be influenced by different physicochemical properties of these surfaces, while Salmonella uses fimbriae and produces cellulose as the main matrix components of biofilms. Their synthesis is co-regulated by a LuxR-type regulator, the agfD (aggregative fimbriae, curli), and adrA genes, respectively. Thus, this study investigated the production of biofilm by Salmonella spp. isolated from raw poultry (breast fillet), purchased in Botucatu, Sao Paulo, Brazil, on glass, polyvinyl chloride, and stainless steel at different temperatures (16 degrees, 20 degrees, 28 degrees, and 35 degrees C). We analyzed the frequency of the agfD and adrA genes and the rdar morphotype at 28 degrees C and 35 degrees C in isolated strains. We found Salmonella in 112 of 240 poultry samples (46.7%), and 62 strains previously isolated from the same kind of food were included in the study on biofilm development, gene expression, and rdar morphotype. All of them were positive for both genes, and 98.3% were able to produce biofilm in at least one temperature. The rates of rdar morphotype at 28 degrees C and at 35 degrees C were 55.2% (96 strains) and 2.3% (4 strains), respectively. Glass was the best material to avoid biofilm production, while Salmonella grew even at 16 degrees C on stainless steel. These results point out the need for more effective sanitizing processes in the slaughter plants in order to avoid the permanence of these bacteria in food and eventual human foodborne diseases.